2021
DOI: 10.3390/ijms22179262
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-Inflammatory Fibronectin-AgNP for Regulation of Biological Performance and Endothelial Differentiation Ability of Mesenchymal Stem Cells

Abstract: The engineering of vascular regeneration still involves barriers that need to be conquered. In the current study, a novel nanocomposite comprising of fibronectin (denoted as FN) and a small amount of silver nanoparticles (AgNP, ~15.1, ~30.2 or ~75.5 ppm) was developed and its biological function and biocompatibility in Wharton’s jelly-derived mesenchymal stem cells (MSCs) and rat models was investigated. The surface morphology as well as chemical composition for pure FN and the FN-AgNP nanocomposites incorpora… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 61 publications
0
4
0
Order By: Relevance
“…AgNPs were verified to have an anti-bacterial ability. In vitro and in vivo measurements showed that FN–AgNPs significantly inhibited the expression of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6), promoted endothelialization for MSCs, and attenuated foreign body responses, demonstrating the potential vascular repair applications of FN–AgNPs [ 73 ]. Graphene oxide decorated with Au nanoparticles (Go–Au) was suggested to be a promising nanocarrier owing to its better biocompatibility and its ability to induce various differentiated cell types for MSCs such as neuron, endothelial cells, osteocytes, and adipocytes [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…AgNPs were verified to have an anti-bacterial ability. In vitro and in vivo measurements showed that FN–AgNPs significantly inhibited the expression of pro-inflammatory cytokines (TNF-α, IL-1β, and IL-6), promoted endothelialization for MSCs, and attenuated foreign body responses, demonstrating the potential vascular repair applications of FN–AgNPs [ 73 ]. Graphene oxide decorated with Au nanoparticles (Go–Au) was suggested to be a promising nanocarrier owing to its better biocompatibility and its ability to induce various differentiated cell types for MSCs such as neuron, endothelial cells, osteocytes, and adipocytes [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…The antimicrobial ability was increased with the formation of a hybrid structure of the collagen, BMP-2, and silver nanoparticles, and the cell adhesion and proliferation were increased by the surface roughness of the scaffold. A 48 h exposure of Wharton’s jelly-derived hMSCs to ∼30 μg/mL of AgNPs (5 nm) conjugated with fibronectin (FN-AgNPs) has been recently demonstrated to induce proliferation with the production of ROS in a low amount ( Hung et al, 2021 ). Significantly, FN-AgNPs also facilitated the migration of hMSCs and showed anti-inflammatory properties.…”
Section: Current Developments Of Nanotechnology In Orthopedic Implantsmentioning
confidence: 99%
“…Of particular interest, it has been found that FN-adsorbed hydrophilic titanium dioxide surface drives the macrophage polarization to anti-inflammatory M2 phenotype through the interaction of FN with macrophage integrins . There is also a finding suggesting that FN-functionalized Ag NPs suppress inflammation in monocytes and improve MSC differentiations, which may be a potential anti-inflammatory surface modification strategy . However, these studies are mainly focused on building material–FN biointerfaces, in which the studied mechanisms toward biomedical applications are mostly related to the FN signaling with cell-surface integrins, and the influence of an intracellular delivery of FN on a biological process, such as inflammation, has not been investigated.…”
Section: Introductionmentioning
confidence: 99%
“…13 There is also a finding suggesting that FN-functionalized Ag NPs suppress inflammation in monocytes and improve MSC differentiations, which may be a potential anti-inflammatory surface modification strategy. 14 However, these studies are mainly focused on building material−FN biointerfaces, in which the studied mechanisms toward biomedical applications are mostly related to the FN signaling with cell-surface integrins, and the influence of an intracellular delivery of FN on a biological process, such as inflammation, has not been investigated. It is a fact that, to present, safe and efficient delivery of protein into cells still remains a challenge.…”
Section: ■ Introductionmentioning
confidence: 99%